Finite time tracking control of mobile robot based on non-singular fast terminal sliding mode. Issue 1 (1st January 2018) - Guo, Xinchen; Liang, Zhenying; Li, Caihong
ABSTRACT: To solve the tracking problem of mobile robot, a hybrid control algorithm based on back-stepping control and non-singular fast terminal sliding mode control is proposed in this paper. The algorithm not only ensures the pose tracking of the robot but also realizes the finite time tracking of the optimal speed by designing the non-singular terminal sliding mode surface. The controller solves the singularity problem in the general terminal sliding mode control. And the advantage of the controller over the general sliding mode controller is that the control input is continuously and approaching to zero. On this basis, we used an RBF neural network to estimate the uncertainties of the system, the stability of the system is proved by Lyapunov stability theory and Barbalat theorem. Finally, the simulation results show that the controller is correct and effective.